2022
DOI: 10.1007/s11096-022-01436-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the time required by pharmacists to prepare discharge medicine lists: a time-and-motion study

Abstract: Background Discharge medicine lists provide patients, carers and primary care providers a summary of new, changed or ceased medicines when patients discharge from hospital. Hospital pharmacists play an important role in preparing these lists although this process is time consuming. Aim To measure the time required by hospital pharmacists to complete the various tasks involved in discharge medicine handover. Method Time-and-motion study design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Our research adds to previous studies that suggested optimisation of software integration 17 and increased utilisation of pharmacy assistants 30 , 31 , 32 can reduce the amount of time pharmacists spend performing time-consuming data entry, allowing them to allocate more time to specialised clinical tasks. Pharmacists suggested a need to improve ieMR software to include the capacity to generate discharge medicine lists, eliminating the need for retyping medicine lists in eLMS.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Our research adds to previous studies that suggested optimisation of software integration 17 and increased utilisation of pharmacy assistants 30 , 31 , 32 can reduce the amount of time pharmacists spend performing time-consuming data entry, allowing them to allocate more time to specialised clinical tasks. Pharmacists suggested a need to improve ieMR software to include the capacity to generate discharge medicine lists, eliminating the need for retyping medicine lists in eLMS.…”
Section: Discussionmentioning
confidence: 58%
“…Data was collected at the GCHHS, incorporating both Gold Coast University Hospital (GCUH) – a tertiary hospital with approximately 750 beds – and Robina Hospital, with approximately 350 beds. 17 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations